Foreign Exchange Exposure and Risk Management Strategies: A Bibliometric Analysis of Global Research Trends (2000-2024) - Della Fauzia Kundari; Imas Purnamasari; Toni Heryana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Research on foreign exchange exposure and risk management strategies has begun to show significant growth over the past two decades. This study aims to map the development of global literature related to foreign exchange exposure through a bibliometric analysis of Scopus-indexed publications from 2000 to 2024. The study population consisted of articles, conference papers, and other scientific publications relevant to the topic. All publications were analyzed using VOSviewer software. Research findings based on bibliometric data show a total of 347 different documents. Publications relevant to this topic have shown a consistent upward trend each year, with the highest number of publications occurring in 2024 with 31 articles. The largest number of authors came from the United States, the United Kingdom, and China. The main results of this study show three important findings. First, research on foreign exchange exposure has experienced significant growth since 2008, in line with increasing global market volatility and the need for companies to implement risk mitigation strategies. Second, the bibliometric visualization identifies seven main research topic clusters: (a) measuring exchange rate exposure, (b) market risk and volatility, (c) hedging strategies using derivative instruments, (d) risk management in multinational corporations, (e) global financial market integration, and (f) the impact of exchange rates on corporate performance. Third, analyses of co-authorship, co-occurrence, bibliographic coupling, and co-citation indicate that research collaboration remains concentrated in developed economies, although contributions from developing countries have begun to increase in recent years. Overall, this study provides a comprehensive overview of the evolution, research focus, and direction of global research development related to foreign exchange exposure and risk management strategies in the context of international economic uncertainty.